PENGARUH PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN PERSEPSI KEADILAN PAJAK SEBAGAI VARIABEL INTERVENING DI KPP PRATAMA SURABAYA SAWAHAN - YUNITA PURWA WARDHANI; MIENATI SOMYA LASMANA (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2014)
This study aims to examine the effect of tax knowledge to taxpayer’s compliance with the perceived tax fairness as an intervening variable in KPP Pratama Surabaya Sawahan. Data was collected through questionnaire method that contains a list of statements about each of the variables studied.Respondents of this study was effective individual taxpayers who derive income from business and/or work freely in KPP Pratama Surabaya Sawahan. Samples are taken of 100 respondents. Analysis of data in this study using the program SmartPLS 2.0. Testing hypotheses using PLS approach, carried out in two stages, namely, testing the outer model and inner model. Outer model test done to prove validity and reliability of all indicators in each variable of the model. Inner model test was conducted to test the effect between variables of the model appropriate to previously defined hypotheses. Result of each test showed: (1) tax knowledge has significant positively effect to perceived tax fairness, (2) perceived tax fairness has significant positively effect to taxpayer’s compliance, (3) tax knowledge has positively and no significant to taxpayer’s compliance, (4) tax knowledge has significant positively to taxpayer’s compliance by perceived tax fairness.